Strengthening health systems worldwide: A new role for the ECDC - Susan Bergner; Isabell Kump (Stiftung Wissenschaft und Politik (SWP), 2021)
The proposal for a European Health Union is currently being discussed by the Council of the European Union and includes the strengthening of the European Centre for Disease Prevention and Control (ECDC) as well as the extension of its mandate. In light of this, the ECDC and the European Union (EU) member states can make the case for a new role for the ECDC. While the political weight of the member states is needed, the ECDC can seize the opportunity of expanding its regional and bilateral partnerships to promote health systems strengthening through development projects. In doing so, the ECDC would be contributing to sustainable development and the 2030 Agenda.
Keywords: 320